“Forest is integral to life”: people-forest relations in the lower river region, the Gambia - Darboe, Sarata; Manneh, Lamin; Stryamets, Nataliya; Prūse, Baiba; Pieroni, Andrea; Sõukand, Renata; Mattalia, Giulia (Frontiers in Forests and Global Change, 2023)
Introduction Forests play a crucial role in the lives of millions of people worldwide by providing material and non-material contributions. Despite forests’ paramount importance from ecological, economic, and cultural perspectives, the long-term relationship between forests and local communities living in their proximity is often an undervalued contribution to our understanding of local ecological knowledge systems and forest changes. Methods We studied the interrelationships between the Mandinka peoples and forests in an understudied area of West Africa, the Gambia’s Lower River Region (LRR). Through 35 semi-structured interviews, we documented the forests’ contributions to local Mandinka peoples and their perception of forest changes. We also used geographic information systems (GIS software) for remote sensing satellite imagery to establish a baseline for these complex connections and changes. Results This research revealed the crucial importance of the forest’s contributions to Mandinka communities and specifically to their psychological well-being. In addition, the interviewees revealed how ongoing socio-economic changes are affecting the human-forest relationship and possibly eroding the local ethnoforestry knowledge in the LRR of the Gambia. The most common forest contributions are those that provide material goods, serving as the driving force in connecting people with the forest, while non-material contributions are eroding due to complex socio-economic changes. Major socio-economic changes are also believed to drive the shift from dense forest to mixed forest and grassland. Discussion In line with the state of the art, the knowledge and perception of changes documented in this article underline the quintessential need to include local communities’ views in shaping forest management, in order to better fine-tune the strategies to safeguard biocultural diversity across forest areas.